Randomized trial of the effectiveness of combined behavioral/pharmacological smoking cessation treatment in Syrian primary care clinics - Ward, Kenneth D. (Addiction, 2012)
AIMS: Effectiveness of nicotine replacement therapy (NRT) for smoking cessation has not been evaluated in low income countries, such as Syria, where it is expensive and not widely available. We evaluated whether nicotine patch boosts smoking cessation rates when used in conjunction with behavioral support in primary care clinics in Aleppo, Syria. DESIGN: Two arm, parallel group, randomized, placebo controlled, double-blinded multi-site trial. SETTING: Four primary care clinics in Aleppo, Syria. PARTICIPANTS: Two hundred and sixty-nine adult primary care patients received behavioral cessation counseling from a trained primary care physician and were randomized to receive six weeks of treatment with nicotine versus placebo patch. MEASUREMENTS: Primary end-points were prolonged abstinence (no smoking after a 2-week grace period) at end of treatment, and 6 and 12 months post-quit day, assessed by self-report and exhaled carbon monoxide levels of <10 p.p.m. FINDINGS: Treatment adherence was excellent and nicotine patch produced expected reductions in urges to smoke and withdrawal symptoms, but no treatment effect was observed. The proportion of patients in the nicotine and placebo groups with prolonged abstinence was 21.6% and 20.0%, respectively, at end of treatment, 13.4% and 14.1% at 6 months, and 12.7% and 11.9% at 12 months. CONCLUSIONS: Nicotine patches may not be effective in helping smokers in low-income countries to stop when given as an adjunct to behavioural support.